Neonates and Infants Discharged Home Dependent on Medical Technology: Characteristics and Outcomes. (October 2016) - Toly, Valerie Boebel; Musil, Carol M.; Bieda, Amy; Barnett, Kimberly; Dowling, Donna A.; Sattar, Abdus
Abstract : Background: Preterm neonates and neonates with complex conditions admitted to a neonatal intensive care unit (NICU) may require medical technology (eg, supplemental oxygen, feeding tubes) for their continued survival at hospital discharge. Medical technology introduces another layer of complexity for parents, including specialized education about neonatal assessment and operation of technology. The transition home presents a challenge for parents and has been linked with greater healthcare utilization. Purpose: To determine incidence, characteristics, and healthcare utilization outcomes (emergency room visits, rehospitalizations) of technology-dependent neonates and infants following initial discharge from the hospital. Methods: This descriptive, correlational study used retrospective medical record review to examine technology-dependent neonates (N = 71) upon discharge home. Study variables included demographic characteristics, hospital length of stay, and type of medical technology used. Analysis of neonates (n = 22) with 1-year postdischarge data was conducted to identify relationships with healthcare utilization. Descriptive and regression analyses were performed. Findings: Approximately 40% of the technology-dependent neonates were between 23 and 26 weeks' gestation, with birth weight of less than 1000 g. Technologies used most frequently were supplemental oxygen (66%) and feeding tubes (46.5%). The mean total hospital length of stay for technology-dependent versus nontechnology-dependent neonates was 108.6 and 25.7 days, respectively. Technology-dependent neonates who were female, with a gastrostomy tube, or with longer initial hospital length of stay were at greater risk for rehospitalization. Implications for Practice: Assessment and support of families, particularly mothers of technology-dependent neonates following initial hospital discharge, are vital. Implications for Research: Longitudinal studies to determine factors affecting long-term outcomes of technology-dependent infants are needed. Abstract : Supplemental Digital Content is Available in the Text.